The defense lawyer : the Barry Slotnick story - Patterson, James, 1947-; Wallace, Benjamin, 1968- (Little, Brown and Company, 2021)
Bronx-native Bernard Slotnick's mantra was that everyone deserved a good defense. And he was the best defender out there. A bold strategist in the courtroom, and a doting husband and father of four at home, 'Liberty's Last Champion' proudly stood up for the unpopular and the controversial, including: John Gotti, head of the Gambino crime family; Joe Colombo Sr., inspiration for The Godfather; Rabbi Meir Kahane, founder of the Jewish Defense League; Bernhard Goetz, the subway shooter. Known for his sharp mind (and his sharp suits). Slotnick, anointed the best criminal lawyer in the United States by The American Lawyer, had a remarkable legal career capped by an extraordinary twelve-year winning streak. From negotiating Melania Trump's pre-nup to representing the Dapper Don, from defending the Subway Vigilante to mediating Bette Midler's bathhouse contract, Slotnick's unparalleled acumen defined a profession, a city, and an era.